A review of the structural performance of prestressed monoblock concrete sleepers in ballasted railway tracks. (October 2022) - El-sayed, H.M.; Fayed, M.N.; Riad, H.S.; Zohny, H.N.
Highlights: Common failure modes of concrete sleepers were deeply analysed. Different design philosophies of concrete sleepers were discussed. The influences of different material additives and geometry parameters were investigated. The relationships between sleepers and elastic track components were explored. The knowledge gaps have been critically defined. Abstract: Prestressed monoblock concrete sleepers (PMCS) in railway ballasted tracks are the most recommended type of sleepers. They experience damage at an increasing rate with the increased demands for higher loads, train speeds, and traffic volume, concluding that an optimal design of this component will have a direct impact on the capital and maintenance funds, track system safety, and reliability. To this end, this study provides a comprehensive review pertinent to the structural performance of PMCS from perspectives including design philosophies, material and geometry properties, and relationships between PMCS and elastic track elements. In this study, the potential directions for improving the structural behaviour of PMCS were identified and analysed, and the gaps in knowledge were determined for further study. The outcomes of this research would contribute to improvements in the current design practices of concrete sleepers and ballasted railway tracks from perspectives including safety, financial value, reliability, and environmental impact.